PERAN KESBANGPOL KABUPATEN SUKABUMI DALAM PENDIDIKAN POLITIK BAGI PEREMPUAN: STUDI KASUS PERSPEKTIF ADMINISTRASI PUBLIK - Kusnadi, Enjang (Mimbar Administrasi Mandiri, 2025)
This study aims to analyze the role of Kesbangpol (National Unity and Politics Agency) of Sukabumi Regency in political education for women from a Public Administration perspective. The research method applied is qualitative, with a case study approach. Data were collected through in-depth interviews with Kesbangpol officials, staff, KPPI leaders, and Bawaslu commissioners, complemented by observations of political education activities and official KPU documents. The results show that Kesbangpol acts as a facilitator, implementer, and coordinator of women’s political education, despite facing challenges such as limited budgets, broad regional coverage, and human resources. The programs positively impact by enhancing political literacy, increasing awareness of rights, and boosting women’s confidence to actively participate in local politics. However, KPU data reveal a gap: out of 650 legislative candidates in Sukabumi Regency (35.3% women), only 8 women (16%) won seats in the 2024–2029 period. The novelty of this study lies in its updated analysis connecting Kesbangpol’s role with actual electoral outcomes, contributing to Public Administration literature while providing practical input for gender-responsive political education policies.